Stress response to laryngoscopy and ease of intubation:comparison between macintosh and (levering) mccoys type laryngoscope - Gotiwale, Kamlesh; Lele, Smita; Setiya, Sushma (International Journal of Research in Medical Sciences, 2017)
Background: Laryngoscopy and intubation is known to cause exaggerated hemodynamic response and increased intracranial pressure. The aim of the study was to compare the hemodynamic response following intubation with mccoys and macintosh blades, to evaluate intubating conditions and to evaluate glottic view during laryngoscopy. Methods: It is a prospective, comparative stody. 100 patients were taken as sample size. Patients undergoing various surgery of age group 20-50 years of both sexes with ASA 1 and ASA 2 were chosen. For odd number patients mccoy laryngoscope blade was used whereas for even number patients macintosh laryngoscope blade for orotracheal intubation. After induction and neuromuscular blockade preintubation pulse and blood pressure was recorded. Orotracheal intubation was attempted at this stage using laryngoscope blade assigned to respective group. Pulse and blood pressure was recorded while the blade was being inserted in vallecula. Similar pulse and blood pressure was taken at 1 minute, 3 minute and 10 minute after laryngoscopy. Ease of intubation was noted by knowing total time required for intubation , need for burp maneuver and occurrence of any complication. Results: Both groups were comparable in terms of age, sex, ASA grade, mallampatti grade. At 3 minutes pulse, systolic and diastolic blood pressures were significantly high with macintosh group as compared to mccoys group. Regarding ease of intubation, it was found that time required for laryngoscopy was significantly longer with the use of macintosh blade as compared to mccoys blade. 34% of patients with macintosh blade required burp manuver as compared to none with mccoys blade. There was no complication with mccoys blade. Conclusions: Less hemodynamic changes was associated with use of mccoys blade. Intubating conditions were better with mccoys blade group as compared with macintosh group.